Mentoring Program on Conducting Research and Writing Scientific Paper for Civil Servant Teachers - Kholiq, Abdul (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
Teachers with the status of civil servants have to write scientific papers for promotion. It is relatively complex for them since they are not used to conducting research or writing research articles to be published in a scientific journal. Therefore, this service was accomplished to assist teachers in carrying out research in their madrasahs and writing scientific papers to be published. The service method employed was Participatory Action Research (PAR) with the approach including 1) Lecturing, 2) Workshop, 3) Review, 4) Action Plan, and 5) Seminar. Furthermore, the objects of mentoring activities were 20 civil servant teachers at private madrasahs in Semarang City. The results of this activity were that teachers could write proposals, carry out research in the classroom, and report the findings in journal articles. Overall, assisted teachers had a 'sensitivity' in recognizing problems in the classroom and analyzing them. Their self-confidence as professional educators developed with the rise of awareness in writing research articles.